Implementasi Data Mining Clustering Tingkat Kepuasan Konsumen Terhadap Pelayanan Go-Jek - Sinta Maria Sinaga; Jaya Tata Hardinata; M. Fauzan (LPPM STIKOM Tunas Bangsa, 2021)
Increasingly high demands for mobility in today's society, activities are also increasingly crowded, especially parents, employees, and even students so it is increasingly difficult to find free time to meet the needs of daily life. So that people need something that can answer and be a solution to the complaint without having to drain time and energy with results that do not disappoint. Gojek is a solution to the complaints of people who do not have much free time and want to relax while waiting for their needs to be met, Gojek is an online application that can be downloaded via a smartphone, has more than six services provided therein but the author only takes some of the services to be standard the level of community satisfaction with Gojek services. The purpose of this study was to determine the level of community satisfaction with Gojek services. One method contained in Data Mining used in this study is the Clustering method. To find out the level of community satisfaction done with interviews / questionnaires 120 people in the city of Pematangsiantar. The benefits are to make it easier for Gojek companies to know how the quality of services provided to the community is based on the level of community satisfaction and improve the quality of services provided to the community.